Granulox—The Use of Topical Hemoglobin to Aid Wound Healing: A Literature Review and Case Series From Singapore. (June 2021) - Loh, Clement; Tan, Qian Ying; Eng, Diane L. K.; Walsh, Stewart R.; Chong, Tze Tec; Tang, Tjun Yip
Chronic wounds are an increasing burden on health care globally, and tissue hypoxia is a common issue in such wounds. Granulox (SastoMed GmbH, Georgsmarienhütte, Germany) is designed to provide wound bases with supplemental oxygen through facilitated diffusion and aid the physiological wound-healing process. It is a topical hemoglobin wound spray that is applied after wound cleaning and debridement to ensure continuous oxygen supplementation for up to 72 hours. Compared with other forms of topical oxygen therapy that require portable devices, Granulox is a spray-on application and the patient experience is similar to the use of a conventional dressing. Current clinical evidence suggests that Granulox aids with both wound healing and with symptom relief in chronic wounds, but current literature is limited by small study populations and further larger studies are required.